IEEE Std 1149.7: What, Why, Where? - José Martins Ferreira (2012)
The IEEE Std 1149.7 holds the promise of great improvements for testing electronic circuits, when used along with other IEEE standards (particularly those that use the IEEE Std 1149.1 for test access and control). In this paper we describe what is the IEEE Std 1149.7, the reasons why we may consider to use it instead of IEEE Std 1149.1, and we highlight the application spectrum where this new standard can be useful.